Natural resources and income inequality in developed countries synthetic control method evidence - Hartwell, Christopher A. 1973-; Horváth, Roman; Horváthová, Eva; Popova, Olga (Leibniz Institute for Eastern and Southeastern European Studies, 2019)
We examine the causal effect of natural resource discoveries on income inequality using the synthetic control method on data from 1947 to 2009. We focus on the natural discoveries in Denmark, Netherlands and Norway in the 1960–1970s and use top 1% and top 10% income share as the measure of income inequality. Many previous studies have been concerned that natural resources may increase income inequality. To the contrary, our results suggest that natural resources decrease income inequality or have no effect. We attribute this effect to the high institutional quality of countries we examine.
Keywords: Geschichte 1947-2009; Einkommensverteilung; Natürliche Ressourcen; Ungleichheit; Niederlande; Norwegen; Dänemark